Game theory for resource sharing in large distributed systems - Sara Riahi; Azzeddine Riahi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In game theory, cooperative and non-cooperative approaches are distinguished in terms of two elements. The first refers to the player's ability to engage: in a non-cooperative context, they are entirely free to make decisions when they make their choices; However, in a cooperative context, they have the opportunity to engage contractually the strategies that should be adopted during the game, that during a phase of discussions held before the game and during combinations which may be formed.In this context, the problem is not so much to predict the outcome of the game between players to leave the benefit of cooperation. To achieve this, and this is the second major difference with the non-cooperative approach, it adopts an axiomatic approach (or normative) by which we set upstream properties a priori reasonable (or desirable) on the outcome of the game. The purpose of this paper is to present briefly the main types of non-cooperative games and the tools that allow them to be analyzed in a complete information context where all aspects of the game are well known to decision makers.